Birleşik Krallık-Avrupa Birliği (AB) Ticaret ve İş Birliği Anlaşması ve Türkiye’nin Gümrük Birliği Modernizasyonu - Durmuş Ali KOLTUK; Filiz KAVAL (Gazi Akademik Bakış)
This study aims to examine the new cooperation model accepted between the European Union (EU) and the United Kingdom after Brexit to Turkey-EU relations, applicability through the modernization of the Customs Union. Two basic questions are asked in this study. The first one is “What were the effects of the Trade and Cooperation Agreement (TCA) signed between the EU and the UK after Brexit on the imports and exports of the parties?” Secondly, “Can the Customs Union Decision accepted between Turkey and the EU in 1996, which had a negative impact on Turkish exporters and businesses, be transformed into the Trade and Cooperation Agreement signed between the EU and the United Kingdom?” Basically, mixed (qualitative-quantitative) research method is used in the study and an evaluation is made on secondary data. In this context, with the modernization of the Customs Union within the scope of the “Trade and Cooperation Agreement”, it is estimated that Turkey's exports to the EU from 41% to 70%, and its imports from the EU will increase from 31% to 40%.